The Effect of Work Environment, OHS, and Job Satisfaction on Employee Performance - Jodie Ridha Arrozak (International Journal of Innovation in Enterprise System, 2021)
Intense competition in Indonesia forces private companies in the defense industry to be more competitive. PT. Z is one of the largest private defense products and equipment manufacturer in Indonesia. To retain competitiveness, PT. Z must provide defense products and equipment with the best quality and deliver it on-time. The quality and on-time delivery of products and equipment fulfillment rely on the performance of employee at PT. Z. Over the last few years, employee performance at PT. Z constantly decreased. The decrease of employee performance can be caused by several factors including work environment, occupational health and safety, and job satisfaction. This research will examine the effect of work environment (WE), occupational health and safety (OHS) and job satisfaction (JS) on employee performance (EP). The analysis was carried out using the PLS-SEM with 120 samples taken from production and engineering division at PT. Z. The result shows that there are positive and significant effect of WE on EP, WE on JS, OHS on JS, and JS on EP. JS also mediates the effect of OHS on EP. On the other hand, OHS does not have a direct effect on EP and JS cannot mediate the effect of WE on EP.